A yeast mating platform for multiplex screening of fungal GPCR–ligand interactions - Giovanni Schiesaro; Melani Mariscal; Mathias Jönsson; Ricardo Tenente; Mathies Brinks Sørensen; Marcus Wäneskog; María Victoria Aguilar-Pontes; Agustina Undabarrena; Marcus Deichmann; Emma E. Hoch-Schneider; Viji Kandasamy; Thomas M. Frimurer; et al. (Proceedings of the National Academy of Sciences, 2025)
Fungi are essential members across ecosystems, yet phytopathogenic fungi pose an increasing risk to crop yields. Despite their ecologic importance, cell–cell communication in fungi is underexplored, partly due to the lack of high-throughput techniques. Here, we developed a Yeast Mating Platform (YeMaP) to investigate the interaction between fungal G protein–coupled receptors (GPCRs) and pheromone peptides. We used YeMaP for high-throughput screening of 8,000 pheromone sequences and identified peptides with improved agonism or antagonism action. We found that these peptides can be applied in a native fungal system such as the plant pathogen Fusarium oxysporum , to control hyphal chemotropism and reduce plant root penetration. Additionally, we utilized YeMaP in a one-pot assay to investigate how abiotic factors influence the communication of multiple pheromone–GPCR combinations and found that the cell–cell communication mediated by the GPCR Ste2 from F. oxysporum signaled robustly across different abiotic factors, while other fungal GPCR–pheromone interactions were more sensitive to changes. Taken together, YeMaP accelerates the identification of fungal GPCR–peptide interactions by enabling one-pot assays, and serves as a model system for studying fungal cell–cell communication.